Negative correlation between interleukin-2 (IL-2) serum with bacterial index in leprosy - Patricia Dian Putri; Luh Made Mas Rusyati; Made Swastika Adiguna (Bali Dermatology and Venereology Journal, 2020)
Background: Leprosy is strongly influenced by the host immunity response. One of the cytokines that play a role in cellular immunity is IL-2. IL-2 will stimulate macrophages to activate phagocytosis and form granulomas, and this occurs in the tuberculoid type of leprosy.Objective: Aim of this study was to verify the IL-2 serum levels are negatively correlated or not with bacterial index in leprosy.Methods: This study was a cross-sectional observational analytic study involving 50 leprosy subjects (41 MB and 9 PB types). Study was conducted at Dermatolovenerology Polyclinic of Sanglah General Hospital from December 2019 to March 2020. Sample was taken using a consecutive sampling method. IL-2 serum levels were measured by ELISA. Result: The mean of IL-2 serum in PB was 75.53±10.32 pg/mL and in MB was 37.59±17.13 pg/mL. Strong negative correlation (r= -0.67; p<0.001) between serum IL-2 levels with bacterial index (CI 95%= 25.96–49.93; p<0.001) was found. Every 1 pg/mL increase in IL-2 serum levels will be accompanied by a decrease in the bacterial index of 0.039 and vice versa. Determinant coefficient shows that 42.2% of bacterial index affected by the IL-2 serum levels. Low IL-2 serum levels were the risk factor of high bacterial index 2.8 times (PR= 2.8; CI 95%= 1.444–5.519; p<0.001).Conclusion: IL-2 serum levels were found to be higher in PB than MB. There was a negative correlation between IL-2 serum levels with bacterial index. Low IL-2 serum levels were the risk factor of a high bacterial index in leprosy patients.